From Eastern European Rooted Immigrant Circle to the Mainstream of American Culture an Alfred Kazin's Transition - Rafał Zygmunt (Language, Culture, Politics)
Tracing the process of immigrants' transition, it appears that in the twentieth century children of Eastern European, mainly Jewish immigrants were trying to get rid of the European past of their parents as quickly as possible in order to take the full advantage of American culture. This attitude brought serious changes in family values, social ties, and religious traditions among immigrants' children, which was vividly presented in Kazin's works. Moving straight toward their American future often meant leaving the Old World heritage and language behind. Many of the immigrant children regarded this type of attitude as another logical step in their development. But although this incorporation into the mainstream of the American culture was fruitful, some of them experienced a deep sense of irreversible loss over their past.